Molecular analysis of the composition of the bifidobacterial and lactobacillus microflora of humans. - McCartney, A L (1996)
The bifidobacterial and lactobacillus populations of fecal samples collected from two human subjects during a 12-month period were studied. The total numbers of bifidobacteria were stable throughout the study period in both subjects, but lactobacillus numbers were less constant. Analysis of the composition of the bifidobacterial populations by using ribotyping or pulsed-field gel electrophoresis to differentiate between bacterial strains demonstrated major differences between the subjects. Subject 1 harbored five strains of bifidobacteria throughout the 12-month period, and one strain was numerically predominant. In contrast, subject 2 harbored a more complex bifidobacterial population (five to six strains per sample) whose composition fluctuated throughout the 12 months. One lactobacillus strain was numerically predominant throughout the study in both subjects. Strains of bifidobacteria and lactobacilli common to both subjects were not detected.